Exploration Of Staff Incentives And Strategy Implementation In Commercial Banks In Kenya - Mkandawire, Nathan Chizotera; Senaji, Thomas Anyanje; Kirimi, Eunice Karegi (Advances in Social Sciences Research Journal, 2020)
Though elegant strategies are formulated by organisations, their successful implementation continues to be elusive. Empirical literature suggests that failure of strategy at implementation state is due to factors such as management competence, leadership and resources. However, little attention has been directed to the relationship between incentives, specifically staff incentives such as pay, oversight, meaningfulness of work, employee growth as well as job security and strategy implementation. In this this exploratory study, we examined the perception of staff incentives and their relationship with implementation of financial inclusion strategy in commercial banks in Kenya using a quantitative survey of 42 respondents drawn from commercial banks in Kenya. Financial inclusion strategies are defined as roadmaps of agreed actions at the national or regional level, which stakeholders chart and pursue to accomplish financial inclusion objectives. The study’s target population was operational managers selected from each bank randomly. We found that staff incentives provided to bank employees ranged from being unsatisfactory to moderately satisfactory and that financial inclusion strategy implementation was also moderately successful in the banks. It was also found that oversight and job security had a linear relationship with financial inclusion strategy implementation (oversight: r = 0.336, p = 0.029; job security: r = 0.685, p < 0.001). Further, the pay negatively affected the probability for successful implementation of financial inclusion strategy – it reduces the likelihood by 50% (exp (B) = 0.53) while job security increased the chances for successful implementation of financial inclusion strategy by a factor of 2 (exp (B) =1.883). In conclusion, based on these preliminary findings banks should consider and improve their pay because it was found to negatively affect the likelihood of successful implementation of financial inclusion strategy. Secondly, since job security was found to increase the probability of successful implementation of financial inclusion strategy management of banks should strive to ensure job security to enable them implement the financial inclusion strategy hence improve the financial performance of the banks. Consequently, the managers should improve on the incentives that were rated as unsatisfactory or low by the employees